TWO SIDES OF THE COIN: A PERSON- AND PROCESS-CENTERED ANALYTICAL APPROACH TO SCHOOL BULLYING PHENOMENON - Aleksandra Tłuściak-Deliowska (Society Register)
Over the past four decades of research on school bullying have produced an extensive body of knowledge about the nature of this phenomenon, its determinants and consequences. Bullying has been examined and explained in individual as well as in contextual terms, and from a wide range of different theories and research methods. In the literature, it can be found some attempts to sort out scientific approaches to bullying. In this article, which should be treated as review-style essay, I will present two complementary approaches to analyzing school bullying, namely (1) person-oriented analytical approach which focuses on analyzing of individual traits and characteristics of children involved in school bullying, and (2) processual analytical approach that emphasizes the processes involved. These approaches were distinguished based on the review of Polish and foreign literature on school bullying.